2020
DOI: 10.2106/jbjs.oa.19.00080
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis Comparing Proximal Row Carpectomy and Four-Corner Arthrodesis

Abstract: Background: The optimal surgical treatment for scapholunate advanced collapse (SLAC) and scaphoid nonunion advanced collapse (SNAC) remains unclear. To inform clinical decision-makers, we conducted a cost-effectiveness analysis comparing proximal row carpectomy (PRC) and four-corner arthrodesis (FCA). Methods: A Markov microsimulation model was used to compare clinical outcomes, costs, and health utilities between PRC and FCA. The model used a 10-year time horizon and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…In this regard, the sequence of chondral destruction caused by SLAC and SNAC wrist has been previously described in four stages: these areas are generally quite similar within these two degenerative wrist diseases [ 26 ]. While four-corner arthrodesis is a widespread surgery used for these two indications, proximal row carpectomy renders another more cost-effective and less surgically demanding surgical technique [ 26 , 27 ]. However, predicted loss of motion and subsequent OA of the more stressed joints are well-known drawbacks of these two surgical methods [ 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the sequence of chondral destruction caused by SLAC and SNAC wrist has been previously described in four stages: these areas are generally quite similar within these two degenerative wrist diseases [ 26 ]. While four-corner arthrodesis is a widespread surgery used for these two indications, proximal row carpectomy renders another more cost-effective and less surgically demanding surgical technique [ 26 , 27 ]. However, predicted loss of motion and subsequent OA of the more stressed joints are well-known drawbacks of these two surgical methods [ 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Direct costs of antibiotics for superficial infection, anesthesia and surgeon payments for incision and drainage surgery for deep infection (see Appendix III), return clinic visits, and electromyography/nerve conduction studies were obtained from the literature [50][51][52] (Table III). Wrist incision and drainage costs were calculated with use of Medicare payments as previously described 53 . Direct costs for wound infection included the surgical cost for incision and drainage, a preoperative return patient visit, and oral antibiotics 51 .…”
Section: Costmentioning
confidence: 99%
“…However, some study groups suggest that FCA may be superior in terms of grip strength, while PRC may be preferable in terms of ROM, postoperative complications, and secondary operations [9][10][11][12]. Some studies indicate that PRC is more cost-effective [13,14], while Daar et al [15] concluded that FCA with cannulated compression screws is the most cost-effective approach. A long-term study reported fewer arthritic changes after FCA versus PRC.…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 99%